Petinosemdeset let profesorice dr. Martine Orožen - Orel, Irena (Slavia Centralis, 2020)
The article describes the scientific research work of dr. Martina Orožen, a prominent Slovenian Slavic.
Keywords: Slovene language; history of Slovene language; Slovenian linguists; anniversaries